Edukasi Kampung Wakaf kepada Masyarakat Desa Mekarjaya, Kabupaten Sukabumi - Asep Nurhalim; Khalifah Muhamad Ali; Salahuddin El Ayyubi; Soni Trison; Aliyya Xaviera (Institut Pertanian Bogor, 2025)
The development of waqf practices implemented so far has become very diverse. However, many people still think that the practice of waqf is limited to the management of 3M (tombs, mosques, and madrasas). Mekarjaya Village has great waqf potential, but its utilization has not been optimally realized because of the limited knowledge of its community. The Kampung Wakaf educational program was organized with the participation of 60 participants, who were the guardians of students from Madrasah At-Tarbiyah, one of the village's waqf assets, aimed at broadening the community's understanding and awareness of the concept and innovative utilization of waqf. The educational activity was conducted in one day, consisting of a material presentation session by the speakers and a discussion and Q&A session before the event was concluded. The result obtained was an increase in the community's knowledge regarding the basic concepts of waqf and its utilization, which was assessed through pre-tests and post-tests conducted at the beginning and end of the activity. Education is expected to support the development of village waqf utilization in a more comprehensive and innovative manner.